ORNAMEN MASJID JAMIK TALUAK KECAMATAN BANUHAMPU KABUPATEN AGAM - Widhya Purwani, Dra. Ernis. M.Pd, Eliya Pebriyeni, S.Pd, M.Sn (Universitas Negeri Padang, 2013)
The purpose of this reseach is to know 1) the name and the shape of the ornament 2) the placement of the ornament 3) the meaning of ornament. The type of reseach is a qualitative descriptive method using. The data type used is a primary and secondary, primary sourced on a mosque ornament while the secondary form is the verbal description of the informant, writting and refernce literatur library and technique of data collection is the observasion, interview and documentation. data analysis was done with data collection, reduction of data, clasification data, display data and draw conclusions. Cheking the validity of the technique of triangulation of data sources. The result of reseach was the name and shape, placement and meaning mosque ornament Jamik Taluak the town Banuhampu Agam. Kata Kunci: nama dan bentuk, penempatan dan makna ornamen